A review of safe water in Malaysia - Abdullah, N. Maizzaty; Mohd Arish, Nur Aini; Salleh, M. Syabil; Amran, M. Aiman Afiq (Penerbit UTHM, 2020)
Safe water supply can altogether enhance the personal satisfaction and is a wellspring of and the condition for economic development and water is at the core of sustainable development. Water resources, and the range of services they provide, underpin poverty reduction, economic growth and environmental sustainability. The issue of water is observed as a general problem for both the urban and the rural population and lack of access to safe and clean water is locked in the heart of the poverty. The study was planned to find out how far the safe water are effective effect to the communities and method to improve the quality the water. Drinking water quality is the great public health concern because it is a major risk factor for high incidence of diarrheal diseases in human body. Water is an essential need of human being. Every person on this planet requires at least 20 to 50 litres of safe water in a day for drinking, cooking and other purposes. According to United Nations (UN) the basic human right is to universal access to Safe water, and an essential step towards better living standards all over the world. Greater accessibility to clean drinking water is a critical need in the area. Collaborative community engagement yielded effective and sustainable interventions.